Progress in Nanoscale Characterization and Manipulation (Springer Tracts in Modern Physics,, 2018)
This book focuses on charged-particle optics and microscopy, as well as their applications in the materials sciences. Presenting a range of cutting-edge theoretical and methodological advances in electron microscopy and microanalysis, and examining their crucial roles in modern materials research, it offers a unique resource for all researchers who work in ultramicroscopy and/or materials research. The book addresses the growing opportunities in this field and introduces readers to the state of the art in charged-particle microscopy techniques. It showcases recent advances in scanning electron microscopy, transmission electron microscopy and helium ion microscopy, including advanced spectroscopy, spherical-corrected microscopy, focused-ion imaging and in-situ microscopy. Covering these and other essential topics, the book is intended to facilitate the development of microscopy techniques, inspire young researchers, and make a valuable contribution to the field.